Modelling production processes in a vehicle recycling plant - Simic, Vladimir (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2012)
The European Directive on end-of-life vehicles (ELVs) fundamentally changed the business philosophy of the European vehicle recycling system, which was exclusively profit-oriented. As the dominant participants of this system, vehicle recycling plants (VRPs) are especially affected by its implementation. For VRPs to successfully respond to the prescribed eco-efficiency quotas, investment will be needed to procure modern sorting equipment as well as to achieve full transformation of their production process. However, before VRPs decide to make this very important investment decision, it is necessary to determine the adequacy of such a decision in detail. Consequently, the following questions become unavoidable: Can modernly equipped VRPs conduct profitable business? Are eco-efficiency quotas actually attainable? How will the new changes in vehicle design influence VRPs? To provide answers to these essential questions, a production planning model of a modernly equipped VRP was first developed and then tested extensively using real data. Based on the answers provided by the proposed model testing analysis it was concluded that VRP transformation is not only necessary but completely justified and that the final success of the ELV Directive is realistic